Total flavonoid contents in bamboo diets and reproductive hormones in captive pandas: exploring the potential effects on the female giant panda (Ailuropoda melanoleuca). Issue 1 (10th April 2019) - Liu, He; Zhang, Chenglin; Liu, Yan; Duan, Hejun
Abstract : This research illustrates the relationship between the total flavonoids content in bamboo diets and the reproductive hormones of female giant pandas from three locations with different birth rates. The flavonoids of bamboo may be related to reproduction and giant pandas might retain a sensitive adaptation to phytoestrogens from bamboo. Abstract: Phytoestrogens have been shown to affect the reproductive hormone levels in both humans and animals. As the main category of phytoestrogens, total flavonoids have a particularly important impact on female animals. To investigate the potential relationship between the total flavonoids in bamboo and the reproductive hormones in female giant pandas, urinary samples and dietary bamboo samples were collected from three main breeding locations (Beijing, Shaanxi and Sichuan). The chemical constituents of the total flavonoids in the bamboo were analysed and quantified using high-performance liquid chromatography coupled with a diode array detector (HPLC–DAD). Estradiol (E2 ), progestin (P), testosterone (T), luteinizing hormone (LH), follicle-stimulating hormone (FSH) and prolactin (PRL) were measured via radioimmunoassay (RIA). The results revealed that the total flavonoids in the bamboo from Sichuan were significantly higher than those in the bamboo from Beijing and Shaanxi, and the concentration in bamboo from Shaanxi was higher than that from Beijing ( P < 0.05). The urinary E2, P, T, FSH and LH levels in pandas from Beijing were significantly lower than those in pandas from Sichuan and Shaanxi ( P < 0.05). The concentrations of six reproductive hormones were positively associated with the total flavonoid contents in bamboo. In addition, the birth rate of pandas in Sichuan was significantly higher than the birth rate of pandas in Beijing and Shaanxi ( P < 0.05). Thus, the flavonoids of bamboo may be related to reproduction and giant pandas might retain a sensitive adaptation to phytoestrogens from bamboo. The total flavonoids of bamboo may play a distinct role in the reproductive success of giant pandas.